Parents' journey through treatment for their child's obesity: a qualitative study. Issue 1 (4th October 2007) - Stewart, L; Chapple, J; Hughes, A R; Poustie, V; Reilly, J J
Abstract : Background: Treatment for childhood obesity is characterised by patient non-attendance and drop-out, and widespread failure to achieve weight maintenance. Qualitative methods may improve our understanding of patient perceptions and so improve treatment for childhood obesity. Aim: To provide insight into the perceptions of parents of obese children as they "journey" from pre-treatment to end of treatment. Methods: We used purposive sampling and studied 17 parents of children (mean (SD) age 8.4 (2.1) years) attending 6-month outpatient treatments for obesity (BMI>98th percentile). Parent's perceptions were explored by in-depth interviews, analysed using Framework methods. Results: Parents were characterised as being unaware of their child's weight, in denial or actively seeking treatment. Parents were consistently motivated to enter treatment due to perceived benefits to their child's self-esteem or quality of life, and weight outcomes appeared typically less important. During treatment parents felt there was a lack of support for lifestyle changes outside the clinic, and noted that members of the extended family often undermined or failed to support lifestyle changes. Parents generally felt that treatment should have continued beyond 6 months and that it had provided benefits to their child's well-being, self-esteem and quality of life, and this is what motivated many to remain engaged with treatment. Discussion: This study may help inform future treatments for childhood obesity by providing insights into the aspects of treatment of greatest importance to parents. Future treatments may need to consider providing greater support for lifestyle changes within the extended family, and may need to focus more on psycho-social outcomes.